THE EFFECT OF PROBLEM-BASED LEARNING (PBL) ON CRITICAL THINKING SKILLS OF STUDENTS AT NURUS SALAM ISLAMIC JUNIOR HIGH SCHOOL - Abdullah, Walib; Maladona, Adi (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on the critical thinking skills of eighth-grade students at Nurus Salam Islamic Junior High School. The background of this study is based on the importance of critical thinking skills as one of the essential skills of the 21st century that must be possessed by students, especially in the context of Islamic education, which emphasizes the development of sound reasoning and logic. This study used a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The research subjects consisted of two classes, namely the experimental class that used the PBL model and the control class that used conventional learning methods. The research instrument was a critical thinking ability test administered at the pretest and posttest. Data analysis was conducted using parametric statistical tests, namely independent t-tests to determine the difference in results between the two groups. The results showed that there was a significant difference in critical thinking skills between students in the experimental group and the control group. Students who learned using the PBL model experienced a higher increase in critical thinking scores compared to students who learned using conventional methods. This shows that the PBL model is effective in developing students' critical thinking skills because it creates an active, collaborative, and challenging learning atmosphere. Thus, the PBL model is recommended as a learning strategy that can improve the quality of the learning process and outcomes, especially in the development of higher-order thinking skills in Islamic school students.